Identifying Malicious Code Through Reverse Engineering - Singh, Abhishek (Advances in Information Security, 2009)
Attacks take place everyday with computers connected to the internet, because of worms, viruses or due to vulnerable software. These attacks result in a loss of millions of dollars to businesses across the world. Identifying Malicious Code through Reverse Engineering provides information on reverse engineering and concepts that can be used to identify the malicious patterns in vulnerable software. The malicious patterns are used to develop signatures to prevent vulnerability and block worms or viruses. This book also includes the latest exploits through various case studies. Identifying Malicious Code through Reverse Engineering is designed for professionals composed of practitioners and researchers writing signatures to prevent virus and software vulnerabilities. This book is also suitable for advanced-level students in computer science and engineering studying information security, as a secondary textbook or reference.